2016
DOI: 10.1186/s13256-016-0915-6
|View full text |Cite
|
Sign up to set email alerts
|

Extremely elevated alpha-fetoprotein due to acute exacerbation of chronic hepatitis B without malignancy: a case report

Abstract: BackgroundAlpha-fetoprotein is produced by a variety of tumors such as hepatocellular carcinoma, hepatoblastoma, and germ cell tumors of the ovary and testes. However, we present a case of significantly elevated serum alpha-fetoprotein without evidence of malignant disease in a patient who is a carrier of chronic hepatitis B.Case presentationA 60-year-old Korean man presented with markedly increased alpha-fetoprotein (2350 ng/mL; normal <5 ng/mL). Various diagnostic evaluations, including computed tomography o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The most common reason for non-malignant AFP elevation is hepatic disease, for example, various forms of hepatitis or cirrhosis and liver trauma [4,5] . Also, liver tissue damage induced by therapeutic measures, for example, radiotherapy [22] or chemotherapy was reported to cause unexpected elevations of serum AFP levels [23] .…”
Section: Discussionmentioning
confidence: 99%
“…The most common reason for non-malignant AFP elevation is hepatic disease, for example, various forms of hepatitis or cirrhosis and liver trauma [4,5] . Also, liver tissue damage induced by therapeutic measures, for example, radiotherapy [22] or chemotherapy was reported to cause unexpected elevations of serum AFP levels [23] .…”
Section: Discussionmentioning
confidence: 99%
“…AFP-L3 exhibits the highest lectin affinity and is commonly seen in patients with HCCs. Some reports have described AFP elevation in the absence of HCC; however, in these cases the AFP levels were only around 2,000 ng/mL 7-10. Viral infections activate multiple proinflammatory mediators such as tumor necrosis factor α, malondialdehyde, and nitric oxide, which recruit immune cells to the liver to generate an antiviral response 11.…”
Section: Discussionmentioning
confidence: 99%
“…Although these increases are typically moderate (<100 ng/mL) [13], higher levels have also been observed in various benign conditions. Yoon et al reported a case of a patient with chronic acute hepatitis B with an AFP value of 2,350 ng/mL in whom the absence of tumor was confirmed [14]. In children and adolescents, elevated concentrations of AFP have been reported in hereditary tyrosinemia type I (values 140 times the URL) [15], in hereditary persistence of AFP (with values 10 times above the URL and reaching 1,000 ng/mL), in ataxia telangiectasia (with values between 20 or 30 times the URL and occasionally reaching 1,000 ng/mL, and rising slightly with age), in ataxia with oculomotor apraxia type II (with values not exceeding 60 ng/mL and not rising with age, in contrast to ataxia telangiectasia) and also modest increases in some cases of ataxia with oculomotor apraxia type I where marker values are usually within the normal range.…”
Section: S39mentioning
confidence: 99%